Material properties and bioactivity of a resin infiltrant functionalized with polyhedral oligomeric silsesquioxanes - Paiva, M. F. [UNESP]; Rizk, M.; Pessan, J. P. [UNESP]; Kreutz, M.; Rohland, B.; Biehl, R.; Stadler, A.; Stellbrink, J.; Wiegand, A. (Elsevier, 2022)
Objectives: To investigate the effect of methacrylate polyhedral oligomeric silsesquioxanes (POSS-8) on various material properties and mineral precipitation potential of a resin infiltrant. Methods: A TEGDMA-based resin infiltrant was mixed with 0.5, 1, 3, 5 or 10 wt% POSS-8 or left unchanged (control). Degree of conversion (DC), water sorption (WS), viscosity, elastic modulus (E-modulus), flexural strength (FS), Knoop microhardness (KHN) and softening ratio (SR) were assessed. Growth of calcium phosphate (Ca/P) precipitates infiltrant-treated bovine enamel and dentin specimens immersed in artificial saliva or artificial dentinal fluid, respectively, for 28 days was analyzed by scanning electron microscopy and energy-dispersive X-ray spectroscopy. For viscosity assessment, pure TEGDMA filled with 0–10 wt% POSS-8 was used. Statistical analyses were performed using ANOVA and Tukey's post-hoc tests (p < 0.05). Results: POSS-8 did not change the flexural strength, water sorption and softening ratio. The apparent degree of conversion was increased at lower concentrations only while E-modulus remained constant in almost all groups. The particles led to a slight decrease of KHN at concentrations below 3%. The effect on viscosity is comparable to the reinforcement effect. Ca/P precipitates formed on dentin specimens treated with POSS-8-filled infiltrant after 4 weeks of immersion, but were not detected on the control infiltrant. The mineral precipitation on enamel was not improved by POSS-8. Significance: POSS-8 particles did not worsen the material properties of the resin infiltrant, while the Ca/P precipitation on dentin was stimulated.
Keywords: Bioactive fillers; Degree of conversion; Elastic modulus; Enamel and dentin lesion; Flexural strength; Knoop hardness; POSS; Resin infiltrant; Viscosity